Predictors of mammography use among Canadian women aged 50–69: findings from the 1996/97 National Population Health Survey - Maxwell, Colleen J. (2001)
BACKGROUND: Screening mammography, although recommended every 2 years for women aged 50–69, is thought to be underused among select groups of Canadian women. METHODS: We used data from the 1996/97 National Population Health Survey to describe current patterns in mammography use (including reasons for not having a mammogram within the 2 years before the survey and future screening intentions) in Canada and to determine factors associated with nonparticipation and time-inappropriate use (mammogram 2 or more years before the survey) among women aged 50–69. RESULTS: Among respondents aged 50–69, 79.1% (95% confidence interval [CI] 76.9%–81.2%) reported ever having had a mammogram, and 53.6% (95% CI 51.4%–55.9%) had had a recent (time-appropriate) mammogram (within the 2 years before the survey). Only 0.6% (95% CI 0.3%–0.9%) of recently screened women reported problems of access, and few reported personal or health system barriers as reasons for not obtaining a recent mammogram. Over 50% of the women who had not had a recent mammogram reported that they did not think it was necessary, and only 28.2% (95% CI 23.8%–32.7%) of those who had never had a mammogram planned to have one within the 2 years following the survey. The rate of time-appropriate mammography varied significantly by province, from 41.1% (95% CI 29.3%–52.9%) in Newfoundland to 69.4% (95% CI 61.3%–77.6%) in British Columbia. Significant predictors of never having had a mammogram included higher age, residence in a rural area, Asia as place of birth, no involvement in volunteer groups, no regular physician or recent medical consultations (including recent blood pressure check), current smoking, infrequent physical activity and no hormone replacement therapy. INTERPRETATION: Despite increases in mammography screening rates since the 1994/95 National Population Health Survey, current estimates indicate that almost 50% of women aged 50–69 have not had a time-appropriate mammogram. Our findings confirm continued low mammography participation rates among older women and those in rural areas, select ethnic groups and women with negative health care and lifestyle characteristics.